Interventions to improve lifestyle and quality-of-life in patients with concurrent mental illness and substance use. (3rd April 2017) - Juel, Anette; Kristiansen, Christina Blanner; Madsen, Nikolaj Juul; Munk-Jørgensen, Povl; Hjorth, Peter
Abstract: Background: Patients with co-existence of psychiatric disorders and substance use have an increased risk of premature death. This is attributable to a higher prevalence of physical comorbidities and a lifestyle related to substance use. Furthermore, they experience low quality-of-life (QoL). Studies addressing lifestyle interventions for these patients are warranted. Aims: To investigate the physical health and QoL in patients with co-existence of psychiatric disorders and substance use, and to analyse for changes in their (a) health, (b) substance use, and (c) QoL after a 24-month health-promotion programme. Further aims were to investigate associations between (a) QoL and number of interventions, (b) QoL and patient characteristics, and (c) QoL and length of participation in the intervention. Methods: In this naturalistic cohort study, 64 non-selected patients were engaged in health-promoting interventions added to contemporary treatments. QoL and clinical variables were measured at the beginning of and continuously during the programme by means of the WHOQoL-Bref questionnaire. Results: At enrolment, the patients' intake of cannabis and alcohol was high. During follow-up, patients consumed significantly fewer caffeinated beverages ( p  = .038) and fast-food meals ( p  = .018), and slept significantly less ( p  = .032). The average dose of antipsychotic medication increased significantly ( p =  .015). QoL was low at enrolment, but improved significantly overall ( p  = .009) and in the psychological ( p  = .020) and environmental domains ( p  = .012) at follow-up. The difference in total QoL was positively associated with the number of interventions attended. Conclusion: This programme shows promise in addressing health promotion for these patients and can easily be integrated into contemporary treatments.